Toll-like receptors: their roles in pathomechanisms of atopic dermatitis - Tamagawa-Mineoka, Risa (Frontiers in Immunology, 2023)
The skin functions as a physical barrier and represents the first line of the innate immune system. There is increasing evidence that toll-like receptors (TLRs) are involved in the pathomechanisms of not only infectious diseases, but also non-infectious inflammatory diseases. Interestingly, it has been demonstrated that TLRs recognize both exogenous threats, e.g. bacteria and viruses, and endogenous danger signals related to inflammation, cell necrosis, or tissue damage. Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease, which is associated with impaired skin barrier function, increased skin irritability to non-specific stimuli, and percutaneous sensitization. The impairment of skin barrier function in AD allows various stimuli, such as potential allergens and pathogens, to penetrate the skin and activate the innate immune system, including TLR signaling, which can lead to the development of adaptive immune reactions. In this review, I summarize the current understanding of the roles of TLR signaling in the pathogenesis of AD, with special emphasis on skin barrier function and inflammation.